ANALYSIS OF THE IMPLEMENTATION OF TRADITIONAL KARO ORNAMENTS IN THE INCULTURATIVE CATHOLIC CHURCH OF BERASTAGI - Viktor Saimar Lamhot Hasugian; Mesra Mesra (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2021)
This research is motivated by the uniqueness of the Karo Berastagi Inculturative Catholic Church, where there are ornaments on the walls of the buildings that adopt the architecture of the traditional Karo traditional house and the incorporation of Christian ornaments. The purpose of this study was to determine the shape, color, meaning and placement of ornaments in the Berastagi Inculturative Catholic Church. The research method in this research is descriptive qualitative. Data collection techniques used are field observations, interviews and documentation. Precisely in the shape of the ornament, the color of the ornament, the meaning of the ornament and the placement of the ornament. This change is also not much different from the traditional Karo onamen in general. ABSTRAK Penelitian ini dilatar belakangi oleh keunikan dari Gereja Katolik Inkulturatif Karo Berastagi dimana terdapat Ornamen-ornamen pada dinding bangunan yang mengadopsi arsitektur pada rumah adat Tradisional Karo dan adanya penggabungan ornamen kekristenan. Tujuan penelitian ini adalah untuk mengetahui Bentuk, Warna, Makna dan penempatan ornamen pada Gereja Katolik Inkulturatif Berastagi. Metode penelitian pada penelitian ini adalah deskriptif kualitatif. Teknik pengumpulan data yang dilakukan adalah observasi lapangan, wawancara dan dokumentasi. Tepatnya pada bentuk ornamen, warna ornamen, makna ornamen da penempatan ornamen. Perubahan tersebut juga tidak jauh beda dari onamen Tradisional Karo pada umumnya. Kata Kunci: Ornamen; Catholic Chuch; Tradisional Karo ;Inkulturatif; Berastagi